Induction of Cell-Associated Chemokines after Endotoxin Administration to Healthy Humans - Olszyna, Dariusz P. (American Society for Microbiology, 2001)
Erythrocytes express the Duffy antigen receptor for chemokines. Endotoxin injection into humans induced high levels of interleukin-8 (IL-8), growth-related oncogene α, and monocyte chemoattractant protein 1 in circulating erythrocytes. IL-8 was also recovered from mononuclear and polymorphonuclear cells. Cell-associated chemokines may more accurately reflect their production than plasma concentrations.